Forest Fallowing among the Appalachian Mountain Folk: An Ethnohistorical Study - Otto, John Solomon (Anthropologica, 2022)
The practice of clearing new fields from forests and abandoning old fields to forest fallow is an ancient agricultural adaptation. Forest fallowing was still practiced in parts of the temperate world by 1900, including the Appalachian mountains. Forest fallowing survived in Appalachia, because it was cheaper to fallow fields than to use costly fertilizers. Forest fallowing, however, required an abundance of forest land for continued success. After 1900, Appalachia lost its surplus forest land to industries and governmental agencies. Trapped on a declining land base, Appalachian mountain farming became maladaptive, resulting in rural depopulation and the demise of forest fallowing.